2014
DOI: 10.1088/0957-4484/25/8/085201
|View full text |Cite
|
Sign up to set email alerts
|

Blending effect of 6,13-bis(triisopropylsilylethynyl) pentacene–graphene composite layers for flexible thin film transistors with a polymer gate dielectric

Abstract: Solution processible poly(4-vinylphenol) is employed as a transistor dielectric material for low cost processing on flexible substrates at low temperatures. A 6,13-bis (triisopropylsilylethynyl) (TIPS) pentacene-graphene hybrid semiconductor is drop cast to fabricate bottom-gate and bottom-contact field-effect transistor devices on flexible and glass substrates under an ambient air environment. A few layers of graphene flakes increase the area in the conduction channel, and form bridge connections between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It is, however, important to note that blends feature mayor drawbacks such as phase segregation, [261] graphene random aggregation, [262] cristallinity loss in the semiconductor matrix [263] and very poor control over graphene deposition. [264] In 2015 we demonstrated [265] an alternative strategy to fabricate multifunctional graphene-polymer hybrid thin-film transistors (PG-TFT) whose transport properties are tunable by varying the deposition conditions of graphene dispersions prepared by the means of UILPE of graphite in NMP.…”
Section: Reviewmentioning
confidence: 99%
“…It is, however, important to note that blends feature mayor drawbacks such as phase segregation, [261] graphene random aggregation, [262] cristallinity loss in the semiconductor matrix [263] and very poor control over graphene deposition. [264] In 2015 we demonstrated [265] an alternative strategy to fabricate multifunctional graphene-polymer hybrid thin-film transistors (PG-TFT) whose transport properties are tunable by varying the deposition conditions of graphene dispersions prepared by the means of UILPE of graphite in NMP.…”
Section: Reviewmentioning
confidence: 99%
“…[4][5][6][7] Some group have tried mixing TIPS-P with other components, like graphene flakes, to modify the crystallization and performance of TIPS-P films. 8 A high hole mobility of 0.8-4.6 cm 2 V À1 s…”
Section: Introductionmentioning
confidence: 99%
“…8 However, these methods require additional processing that is not fully compatible with mass production. For this reason, they are less desirable for practical device applications that demand simple, low-cost fabrication.…”
mentioning
confidence: 99%
“…[17] Graphene would benefit greatly from these characteristics, and because of this reason several attempts of combining these two types of materials have been reported in the literature. [18][19][20][21][22][23][24][25] These include multi-step procedures based on the subsequent deposition of a graphene and the polymeric semiconductor via spin-coating, ink-jet printing or thermal evaporation. [22,23,26] In particular, Torrisi and co-workers fabricated the active channel of a transistor by successive printing of graphene ink and poly[5,5′-bis(3-dodecyl-2-thienyl)-2,2′-bithiophene (PQT-12), reaching high electrical performances (mobility of 100 cm²/Vs).…”
Section: Introductionmentioning
confidence: 99%
“…[18,24,25] In particular, it was recently demonstrated that liquid-phase exfoliated graphene can be codeposited with a polymeric semiconductor and used in thin-film transistors in order to boost the ambipolar character of the polymer. [18] While this method is interesting, it does suffer from several drawbacks, including phase segregation between the two components, [18] graphene random aggregation, [19] crystallinity loss in the semiconductor matrix [20] and poor control over graphene deposition. [21] One interesting approach could rely on the simultaneous blending of the OSCs with graphene during sonication-assisted exfoliation of graphite powder into graphene nanosheets, with OSCs acting as a dispersion stabilizing agents (DSAs) and preventing the re-aggregation of the exfoliated graphene flakes, ultimately enabling the production of homogeneous bicomponent dispersions.…”
Section: Introductionmentioning
confidence: 99%